The Effect Of 5S Training (Seiri, Seiton, Seiso, Seikatsu, Shitsuke) on Improving Student Competence in the Nursing Department Of SMK Sehati Karawang - Nurwansyah, Atikah; Syaodih, Erliany; Handayani, Nining (ProBisnis : Jurnal Manajemen, 2025)
This study aims to analyze the effect of 5S training (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) on improving student competency in the Nursing Department of SMK Sehati Karawang. The background of this study is based on the gap in competency between the needs of the health industry and the limited abilities of students, especially in terms of work efficiency, discipline, and practical skills. The method used is a quantitative approach with an experimental design, comparing the competency of students who have participated in 5S training and those who have not. Data were collected through questionnaires and observations of 43 grade XI students. The results showed that 5S training had a significant effect on improving the competency of nursing students. All 5S elements have been proven to provide a positive contribution in shaping technical skills, professional attitudes, and student work efficiency. Thus, 5S training can be used as an effective strategy in supporting the development of human resources in the field of nursing since the vocational high school level.